A Study Analysis and Survey of Various Contact Centre Solutions - Pandit, A; Manjula, R (International Journal of Computer Sciences and Engineering, 2025)
Any telecommunication contact centre manage several million calls per day. Calls mostly part arrive on passages and are then dealt with by voice entryways. The non-self-served calls are then sent to a call administration framework based on an ICR, which helps with directing the calls empowering call sharing. This mechanism helps the routing externally and lets the call to arrive in required part of the network. Previously, only voice access was provided by contact centre, but now, they merged various channels such as video, voice, fax, SMS/MMS, WEB and email, etc. It seamlessly integrates various service strategies inside enterprises, so that consumers can communicate with organizations conveniently. Various enterprises such as Genesys, CISCO, Avaya, Huawei and many more have their own contact center solution to establish a customer center service architecture that integrates various departments. In this paper, we will give a detailed explanation of different enterprise contact center architectures related to various factors. A sum of 25 working professionals had demonstrated enthusiasm for our overview that incorporates professionals belonging to different Information Technology sector. The outcomes depict the architectural analysis of the contact centre, which are generally used by the professionals.